Intermittent hypoxia does not increase exercise ventilation at simulated moderate altitude - Katayama, K.; Sato, K.; Hotta, N.; Ishida, K.; Iwasaki, K.; Miyamura, M. (International Journal of Sports Medicine, 2007)
Recent human studies have shown that resting hypoxic ventilatory response (HVR), which is an index of ventilatory chemosensitivity to hypoxia, increased after short-term intermittent hypoxia at rest. In addition, intermittent hypoxia leads to increases in ventilation and arterial oxygen saturation (SaO2) during exercise at simulated high altitude, with the increase in ventilation correlated to the change in HVR. However, no study has been made to clarify the relationship between ventilatory chemosensitivity and the exercise ventilation at moderate altitude following intermittent hypoxia during a resting state. The purpose of the present study, therefore, was to elucidate whether intermittent hypoxia at rest induces the increase in ventilation during exercise at moderate altitude that is accompanied by an increase in hypoxic chemosensitivity. Eighteen trained male runners were assigned to three groups, i.e., the first hypoxic group (H-1 group, n = 6), the second hypoxic group (H-2 group, n = 6), and a control group (C group, n = 6). The hypoxic tent system was utilized for intermittent hypoxia, and the oxygen levels in the tent were maintained at 15.5 ± 0.1 % (simulated 2500 m altitude) for the H-1 group and 12.3 ± 0.2 % (simulated 4300 m altitude) for the H-2 group. The H-1 and H-2 groups spent 1 hour per day in the hypoxic tent for 1 week. Maximal and submaximal exercise tests while breathing 15.5 ± 0.01 % O2 (simulated altitude of 2500 m) were performed before and after intermittent hypoxia. Resting HVR was also determined in each subject using a progressive isocapnic hypoxic method. In the H-2 group, HVR increased significantly (p < 0.05) following intermittent hypoxia, while no change in HVR was found in the H-1 or C group. Neither ventilation nor SaO2 during maximal and submaximal exercise at a simulated altitude of 2500 m were changed in either group after 1 hour per day for 1 week of intermittent hypoxia. These results suggest that the change in resting hypoxic chemosensitivity after short-term intermittent hypoxia does not affect ventilation during exercise at moderate altitude.